Protective effects of biochanin A on PC12 cells against Aβ and L-glutamate neurotoxicity - Tan, Ji Wei (2013)
Alzheimer's disease (AD) is characterised by the production of the β-amyloid protein (Aβ) and progressive loss of neurons in the brain. It is considered one of the major neurodegenerative diseases and there is often an association with an excessive amount of glutamate that can lead to excitotoxicity. Estrogen has been previously studied and reported to decrease the risk and delay the onset and progression of Alzheimer's disease. However, estrogen intake increases the risk of unexpected side effects such as heart disease and breast cancer. As such, more attention is being paid towards the usage of phytoestrogens as an alternative solution to replace estrogen. Biochanin A, a phytoestrogen compound found mainly in Trifolium pretense (commonly known as red clover),is a commercial nutraceutical that is available for women who suffer from postmenopausal symptoms. However, its beneficial potential towards human health still remains unexplored. Therefore, biochanin A was used in the present study as a potential alternative to estrogen replacement therapy by investigating its neuroprotective ability and its potential mechanisms in cultured PC12 cells. MTT cell viability assay and LDH release test was used to evaluate the cytotoxic effect of Aβ25–35 and L-glutamate on the cells. Flowcytometry and fluorescent microscopy were performed for qualitative and quantitative analysis of Aβ25–35-induced and L-glutamate-induced cell death. Measurements of caspase-3, 8 and 9 activity were made using caspase colorimetric kits. The mitochondrial membrane potential (MMP) was accessed using spectrofluorometric assessment of rhodamine dye and Western blot analysis was used to measure the pro- and anti-apoptotic protein levels. The results showed that exposure of PC12 cells to either Aβ25–35 or L-glutamate alone caused significantly lower cell viability and higher LDH release and apoptotic activity. However, all of these adverse effects were markedly inhibited in the presence of biochanin A. In addition, biochanin A also recovered the loss of MMP in Aβ25–35-treated PC12 cells by regulating the level of pro-apoptotic (Bax and cytochrome c) and anti-apoptotic (Bcl-2) proteins. In conclusion, the protective effect of biochanin A was demonstrated in the inhibition of apoptosis induced by Aβ25–35 and L-glutamate. Specifically, the apoptosis inhibition of biochanin A involved the prevention of mitochondrial mediated apoptotic processes in the cell. Hence, the present study can serve as a basic platform to further study the effects of biochanin A as it could be developed into a potential treatment agent for AD and other related neuronal degenerative diseases.